2011
DOI: 10.1182/blood-2010-04-278853
|View full text |Cite
|
Sign up to set email alerts
|

The Hsp90 inhibitor IPI-504 overcomes bortezomib resistance in mantle cell lymphoma in vitro and in vivo by down-regulation of the prosurvival ER chaperone BiP/Grp78

Abstract: IntroductionMantle cell lymphoma (MCL) represents ϳ 5%-10% of all nonHodgkin lymphomas. It is characterized by the expansion of mature B-clonal lymphocytes harboring the t(11;14)(q13;q32) translocation, which induces overexpression of cyclin D1, and consequent cell cycle deregulation. In addition, MCL tumor cells carry a high number of secondary chromosomal and molecular alterations affecting proteins involved in cell cycle progression, senescence, and cellular response to DNA damage. 1 The prognosis for this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
91
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(96 citation statements)
references
References 49 publications
5
91
0
Order By: Relevance
“…Moreover, we have demonstrated that after bortezomib treatment BiP/GRP78 is induced in the bortezomib-resistant cell lines OCI-LY8 and SUDHL-4, as well as in multiple myeloma and mantle cell lymphoma. 12,48 The selective inhibition of BiP/GRP78 by siRNA significantly overcomes the constitutive resistance to bortezomib and enhances cell toxicity in response to proteasome inhibition, suggesting an important role for BiP/ GRP78 in the mechanisms of response to bortezomib. Moreover, some treatments, such as vomitoxin and epigallocatechin gallate, may reduce BiP/GRP78 transcription 49 and can be used to increase bortezomib cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we have demonstrated that after bortezomib treatment BiP/GRP78 is induced in the bortezomib-resistant cell lines OCI-LY8 and SUDHL-4, as well as in multiple myeloma and mantle cell lymphoma. 12,48 The selective inhibition of BiP/GRP78 by siRNA significantly overcomes the constitutive resistance to bortezomib and enhances cell toxicity in response to proteasome inhibition, suggesting an important role for BiP/ GRP78 in the mechanisms of response to bortezomib. Moreover, some treatments, such as vomitoxin and epigallocatechin gallate, may reduce BiP/GRP78 transcription 49 and can be used to increase bortezomib cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…6,9,10 The inhibition of proteasome may have sensitized the DLBCL cells to the cytotoxic action of the chemotherapy. Other- wise, bortezomib exhibits NF-B-independent cytotoxicity in a wide range of different tumor types 48,[51][52][53] and affects many additional pathways that may be differently used by ABC and GCB subtypes. 54 For the first time in the literature we describe the prognostic impact of BiP/GRP78 expression in a homogenous series of DLBCL, all treated with R-CHOP, with a mean follow-up of 2.9 years.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study revealed that there was an association between loss of sensitivity to the proteasome inhibitor and upregulation of the prosurvival chaperone GRP78 in mantle cell lymphoma samples and cell lines (23). In addition, Kern et al (24) indicated that bortezomib-resistant solid tumor PC-3 and HRT-18 cell lines were capable of secreting high amounts of GRP78.…”
Section: Discussionmentioning
confidence: 99%
“…Such dissociation generates a potent transcription factor for UPR gene expression activating signaling pathways to maintain homeostasis (HOTAMISLIGIL, 2010;PFAFFENBACH;TODD;GLIMCHER, 2008). Induced HSPA5 has been used as possible activation markers of the antiapoptotic and antiproliferative agents in tumor cells creating a mechanism of resistance (KIM et al, 2006;LIU et al, 2007;MILOSZEWSKA et al, 2010;ROSATI et al, 2010;ROUE et al, 2011;TAN et al, 2011). On the other hand, the induction of anti-HSPA5 functions as an apoptotic protein, forming caspase 7 and 12 complexes, keeping them inactive and blocking their proapoptotic function (REDDY et al, 2003).…”
Section: Resultsmentioning
confidence: 99%